The Effect of Murotal Al-Qur'an Therapy on Efforts to Reduce High Blood Pressure in Pregnant Women at Syahruddin Clinic) - Jahriani, Nani; Lestari, Ika; Nurjanah; Fitria, Aida; Suriyani, Elvi (International Journal of Public Health Excellence (IJPHE), 2022)
The Qur'an is the revealed word of Allah SWT, which is regarded as a miracle. It was revealed to the Prophet Muhammad SAW. The Qur'an is a book that is believed to be true, and its recital is considered an act of worship. Al-Murotal is a recitation of the verses of the Qur'an, the purpose of which is to preserve the Qur'an by recording the reading of the Qur'an. It is a well-established fact that there are specific laws of reading (tajweed) that must be adhered to when reciting the Qur'an. Accordingly, the objective of utilizing recording media is to reinforce the preservation of the Qur'an. The recitation of the Qur'an has been demonstrated to have a beneficial effect on a range of ailments, including those affecting the heart and the body, as well as those pertaining to the afterlife. Furthermore, the Qur'an serves as a remedy for a multitude of human afflictions, acting as both a medicine and an antidote to ailments of the mind and body. Listening to Murotal Qur'an has been demonstrated to have a significant impact on a range of ailments, largely due to the influence of perfect harmony in the repetition of words and letters, the impact of balanced rhythm on the verses of the Qur'an, the impact of information on each verse, and the beautiful harmonization. The pregnant women at the Syahruddin Clinic who are suffering from high blood pressure are unaware that there are alternative treatments available to them besides medication. They are not informed that listening to Murotal Al-Qur'an can help to reduce their high blood pressure. This information has been obtained from interviews with pregnant women who are afraid of taking drugs to reduce their high blood pressure during pregnancy.